Can hydradenitis suppurativa be associated with inflammatory joint involvement? Report of a case series and review of the literature (Dermatology Reports, 2023)
Dear Editor, Hidradenitis suppurativa (HS) or acne inversus, is a chronic inflammatory cutaneous disease with a significant negative impact on the patient’s quality of life, from a psychological, social and occupational point of view. The disease mainly affects the female sex and occurs between puberty and 40 years of age. It is estimated that in Europe the prevalence of the disease in the general population is 1%. Recent studies have shown a high incidence of inflammatory arthritis, in particular spondyloarthritis, in patients with HS.2 In this report, we present 18 cases of patients with hidradenitis suppurativa, visited at the San Gallicano Dermatological Institute, who presented joint symptoms. [...]